2016
DOI: 10.1038/hdy.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of allelic interactions among Pto-miR257 and its targets and their effects on growth and wood properties in Populus

Abstract: MicroRNAs (miRNAs) have important roles in the regulation of genes; however, for trees few studies have explored the potential impact of the interactions between miRNAs and their target genes. Here, we performed transcript profiling and association genetics (single-SNP, haplotype-based and multi-SNP associations) to study the genetic regulatory relationship of Pto-miR257 and its 12 target genes in 435 individuals of a natural population of Populus tomentosa. Expression profiling of Pto-miR257 and its targets s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Wood formation comprises several continuous biological processes [1] that require multiple molecular regulatory mechanisms to synergistically regulate the expression of many genes related to various processes of wood formation [5,8,39]. Although numerous miRNAs involved in the regulation of speci c biological processes in wood formation have been identi ed thus far [12][13][14][15][16][17][18], how many miRNAs exist and the molecular functions these miRNAs in the diverse processes of wood formation remain unclear. The vertical segments of the less than one-year-old poplar that include all processes of wood formation and that can be divided into three phases-beginning, middle, and late phases of wood formation [25,26] -have been used to investigate the dynamics of the molecular regulatory mechanisms underlying diverse phases of wood formation [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wood formation comprises several continuous biological processes [1] that require multiple molecular regulatory mechanisms to synergistically regulate the expression of many genes related to various processes of wood formation [5,8,39]. Although numerous miRNAs involved in the regulation of speci c biological processes in wood formation have been identi ed thus far [12][13][14][15][16][17][18], how many miRNAs exist and the molecular functions these miRNAs in the diverse processes of wood formation remain unclear. The vertical segments of the less than one-year-old poplar that include all processes of wood formation and that can be divided into three phases-beginning, middle, and late phases of wood formation [25,26] -have been used to investigate the dynamics of the molecular regulatory mechanisms underlying diverse phases of wood formation [26].…”
Section: Discussionmentioning
confidence: 99%
“…miR528 promotes rice owering by repressing OsRFI2 under long-day conditions [11]. Presently, although some miRNAs, such as miR875 [12], ptr-miR397a [13], amg-miR166 [14], Pto-miR257 [15], Pto-MIR475b [16], and miRNA156 [17], have been identi ed to participate in different processes of wood formation [14,18], no investigation has been reported on the dynamics of miRNAs and their biological functions involved in diverse phases of wood formation in tree species.…”
Section: Introductionmentioning
confidence: 99%
“…E‐map‐derived MSAP markers were selected to perform the association analysis with the same nine phenotypic traits in natural population by unified mixed linear model (MLM) in Tassel v.2.0 (Yu et al , ; Bradbury et al , ). All associations in natural population took membership probability ( Q ) and pairwise kinship ( K ) into consideration as covariates to evaluate the effects of population structure and relatedness among individuals, unless stated otherwise (Chen et al , ). The significance thresholds for MSAP association analysis in both populations were defined as P < 0.001.…”
Section: Methodsmentioning
confidence: 99%
“…Target gene prediction and transcriptome sequencing suggested that miR257 and its 12 potential target genes control wood formation and tree growth. SNP association analysis to explore the functions of Pto -miR257 and its 12 target genes revealed a significant epistatic interaction between Pto -miR257 and these genes, expanding our understanding of gene regulation and the mechanisms underlying how miRNA-target interactions affect phenotypic variation ( Chen B. et al, 2016 ).…”
Section: Growth and Developmentmentioning
confidence: 99%